The Effect of Brand Knowledge, Electronic Word of Mouth and Product Quality on Purchasing Decisions in E-commerce - Kurniawati, Lathifah; Nuvriasari, Audita (Research Horizon, 2024)
This study aims to analyze the influence of Brand Knowledge, Electronic Word of Mouth (eWOM), and Product Quality on Purchase Decisions for Jiniso products on Shopee. The sampling technique used was purposive sampling with a total of 100 respondents. The data analysis method utilized is multiple linear regression analysis. The results show that Brand Knowledge does not have a significant effect on Purchase Decisions for Jiniso products on Shopee. Meanwhile, eWOM has a positive and significant effect on Purchase Decisions, indicating that online reviews and recommendations from other consumers can increase purchase interest. Additionally, Product Quality also has a positive and significant effect on Purchase Decisions, suggesting that consumers' perception of the quality of Jiniso products plays an important role in the decision to buy. These findings highlight the importance of eWOM and product quality in marketing strategies to enhance consumer purchase decisions.